Business Building Strategies: Adaptive, Collaborative, Dynamic, and Sustainable in the Digital Era - Aang Gunawan; Yuliantini Yuliantini; Olfebri Olfebri; Lira Agusinta (Siber Nusantara Research, 2026)
The development of digital technology has driven significant changes in the business world, requiring organizations to have the ability to adapt, collaborate, innovate, and apply sustainability principles to survive and thrive. A national seminar entitled